Effect of Flash Heating Pasteurization on Coliform Bacteria in Breast Milk Donor from a Household Setting - Choiriyah, Muladefi; Merdikawati, Ayut; Astari, Asti Melani; Rahmawati, Widya; Handayani, Dian (Indonesian Journal of Human Nutrition, 2025)
Donor-expressed breast milk is a recommended alternative in particular circumstances, such as premature birth and maternal mortality. Currently, donor breast milk practices posted on social media platforms have increased, often without adherence to standard safety procedures, which raises concerns about bacterial and viral transmission. Coliform contamination in expressed breast milk is often attributed to insufficient sanitation during the cleaning of breast milk bottles. This study aimed to examine the presence of Coliform bacteria in donor-expressed breast milk before and after pasteurization using the flash heating technique. This study used a quasi-experimental pre-post-test design. The samples consisted of donor-expressed breast milk obtained from registered donors whose infants were younger than 12 months and who had completed the required health screening. Breast milk samples were examined before and after pasteurization using the Most Probable Number (MPN) method. Based on the analysis of 9 expressed breast milk samples, the results showed a decrease in the mean Coliform bacterial count after pasteurization, although this decrease was not statistically significant (p-value = 0.090). In conclusion, the flash heating pasteurization procedure decreases the quantity of coliform bacteria in donor-expressed breast milk.